DOAC versus warfarin in patients with atrial fibrillation and stage IV-V chronic kideny disease including patients on dialysis. (14th October 2021) - Wartanian, A; Lewinter, C; Edfors, R
Abstract: Introduction: Patients with atrial fibrillation (AF) and severe chronic kidney disease (CKD) were excluded from most phase III randomized controlled trials (RCTs) of direct oral anticoagulants (DOACs). Evidence of warfarin versus DOAC in the AF population with stage IV-V CKD is therefore limited. Aim: To evaluate the effectiveness and safety of DOAC compared with warfarin on this population including dialysis patients. Methods: A systematic review and meta-analysis of RCTs and observational studies involving AF patients with stage IV-V CKD treated with warfarin versus DOACs were conducted to evaluate the following outcomes: stroke (ischemic and hemorrhagic) or systemic embolism (SE), all-cause mortality, major bleeding, gastrointestinal (GI) bleeding, and intracranial bleeding. If the heterogeneity between studies was moderate to high calculated as the I 2 ≥50%, a meta regression was undertaken between baseline characteristics and the study outcomes. We conducted a literature search using key words related to AF, severe CKD, DOAC and warfarin in PubMed, Embase and Cochrane Library. Results: Nine studies were included in the meta-analysis. Compared to warfarin, DOAC was significantly associated with a reduced risk of stroke or systemic embolism (SE) (risk ratio [RR] = 0.69; 95% confidence interval [CI] 0.50–0.95) (Figure 1), intracranial bleeding (RR=0.54; 95% CI 0.35–0.84) and hemorrhagic stroke (RR=0.39; 95% CI 0.16–0.95). There was no significant difference between DOACs and warfarin in the risk of all-cause mortality (RR=0.80; 95% CI 0.57–1.13), major bleeding (RR = 0.70; 95% CI 0.44–1.11) (Figure 2) and GI bleeding (RR=0.76; 95% CI 0.56–1.02). For the outcome stroke or SE, dabigatran (compared with apixaban) significantly eliminated the net effect of DOAC as compared with warfarin (coefficient, 0.8; P=0.003). Regarding major bleeding, rivaroxaban and dabigatran both eliminated the DOAC effect from the meta-analysis as compared to apixaban (P=0.01 & P<0.0001). Dabigatran significantly increased the risk of GI bleeding in comparison to apixaban (coefficient, 0.48; P=0.002) in comparison with the overall similar effect of warfarin in the meta-analysis. Conclusion: Among patients with AF and stage IV or V CKD including dialysis patients, DOAC appears to have similar or better effectiveness and safety compared to warfarin. Funding Acknowledgement: Type of funding sources: None.